Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/ajg.2017.423
|View full text |Cite
|
Sign up to set email alerts
|

Depression Is Associated With More Aggressive Inflammatory Bowel Disease

Abstract: Baseline depression is associated with a higher risk for aggressive IBD at follow-up. A single question is not a sensitive method of assessing depression. Providers should consider administering the PHQ-8 to capture those at greater risk for aggressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 37 publications
(34 reference statements)
4
126
2
4
Order By: Relevance
“…Furthermore, in the present survey, psychological distress was associated with several important clinical parameters: active disease, hospitalization, presence of fistulas, perianal disease, pain, and fatigue and the current use of steroids, opioids, and psychotropics. This is in line with the findings of previous studies showing that poor mental health is associated with disease flares and a generally poorer IBD prognosis . Poor mental health has also been previously reported as a significant predictor of hospitalization, readmission, and increased risk of surgery in those with IBD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, in the present survey, psychological distress was associated with several important clinical parameters: active disease, hospitalization, presence of fistulas, perianal disease, pain, and fatigue and the current use of steroids, opioids, and psychotropics. This is in line with the findings of previous studies showing that poor mental health is associated with disease flares and a generally poorer IBD prognosis . Poor mental health has also been previously reported as a significant predictor of hospitalization, readmission, and increased risk of surgery in those with IBD.…”
Section: Discussionsupporting
confidence: 92%
“…The bidirectional links between mental and physical health in IBD have also been established: Baseline IBD activity is associated with a nearly sixfold increase in the risk of anxiety over a period of 2 years, while anxious patients in IBD remission at baseline have a greater need for steroids, escalation of therapy, or IBD flare over time than those without anxiety. Moreover, the course of IBD is negatively affected by mental illness, resulting in more frequent flare ups, a more aggressive presentation, hospital readmissions, and increased risk of surgery …”
Section: Introductionmentioning
confidence: 99%
“…1518 Anxiety and depression rates were comparable to published rates. 19, 20 Psychosocial complexity influenced the IBD course. 21 Less than one half of our cohort had active IBD at baseline with psychosocial factors adversely impacting quality of life and medical utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In database studies, a pre‐existing diagnosis of clinical depression is associated with adverse outcomes in IBD . A recent high‐quality prospective cohort study of 4314 patients with IBD over 2 years found significant associations between depressive symptoms and increased risk of multiple adverse outcomes, including relapse, hospitalization, requirement for biologicals and surgery . Further, another prospective study of 2007 patients found that depressive symptoms expedited clinical recurrence .…”
Section: Epidemiologymentioning
confidence: 99%
“…Notably, depressive symptoms occur in more than 20% of people with IBD, which is approximately two to four times more common than in the general population . As well as reduced quality of life, the co‐morbidity of depressive symptoms and IBD is associated with poor biomedical outcomes, including increased risk of IBD relapse, hospitalization and surgery .…”
Section: Introductionmentioning
confidence: 99%